2013
DOI: 10.1586/17476348.2013.814385
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of high-dose ciclesonide for the treatment of severe asthma

Abstract: Asthma severity is classified according to the level of treatment required to control symptoms. Inhaled corticosteroids are the recommended first-line therapy for the treatment of persistent asthma, and when asthma remains uncontrolled, one option is to increase the inhaled corticosteroids dose. However, there is a concomitant risk of increasing local and systemic adverse events, which may impact patient adherence and physician prescribing practices. Ciclesonide is delivered as a prodrug, has high peripheral l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…[8,9] The side effects of normal ICS use are modest, including hoarseness and oral ulcers, [10,11] whereas high-dose and sustained use of ICS is associated with more serious adverse effects. [1215] However, many studies have found heterogeneity in the therapeutic responses to ICS among asthma patients who show poor improvements in the forced expiratory volume at one second (FEV 1 ), even though they are highly compliant with medication use. [4,16] Thus, identifying those patients who do not benefit from ICS and modifying their treatment regimens to improve health outcomes would be meaningful.…”
Section: Introductionmentioning
confidence: 99%
“…[8,9] The side effects of normal ICS use are modest, including hoarseness and oral ulcers, [10,11] whereas high-dose and sustained use of ICS is associated with more serious adverse effects. [1215] However, many studies have found heterogeneity in the therapeutic responses to ICS among asthma patients who show poor improvements in the forced expiratory volume at one second (FEV 1 ), even though they are highly compliant with medication use. [4,16] Thus, identifying those patients who do not benefit from ICS and modifying their treatment regimens to improve health outcomes would be meaningful.…”
Section: Introductionmentioning
confidence: 99%
“…Responsiveness to ICS is generally much lower in smokers than nonsmokers with asthma 12. Data published by Tomlinson et al13 demonstrate that, compared with nonsmokers, smokers with mild persistent asthma are insensitive to the therapeutic effect of low-dose ICS.…”
Section: Discussionmentioning
confidence: 99%
“…Ciclesonide quickly gets metabolized in the lungs but rarely becomes activated in the oropharynx, and thus shows little systemic and topical side effects (115). Satisfactory therapeutic efficacy and safety profiles of ciclesonide in severe asthma have been demonstrated by clinical trials (115,116). However, it is noteworthy that extremely large dose of ICS may increase the risk for adverse effects, including adrenal suppression, and growth retardation in children.…”
Section: Icsmentioning
confidence: 99%